Activation of promoter P4 of the autonomous parvovirus minute virus of mice at early S phase is required for productive infection - Deleu, Laurent; Rommelaere, Jean (Journal of virology, 1999)
Autonomous parvoviruses are tightly dependent on host cell factors for various steps of their life cycle. In particular, DNA replication and gene expression of the prototype strain of the minute virus of mice (MVMp) are closely linked to the onset of host cell DNA replication, pointing to the involvement of an S-phase-specific cellular factor(s) in parvovirus multiplication. The viral nonstructural protein NS-1 is absolutely required for parvovirus DNA replication and is able to transcriptionally regulate parvoviral and heterologous promoters. We previously showed that the promoter P4, which directs the transcription unit encoding the NS proteins, is activated at the onset of S phase. This activation is dependent on an E2F motif in the proximal region of promoter P4. An infectious MVM DNA clone was mutated in the E2F motif of P4. The wild type and the E2F mutant derivative were tested for their ability to produce progeny viruses after transfection of permissive cells. In the context of the whole MVMp genome, the E2F mutation abolished P4 induction in S phase and inactivated the infectious molecular clone, which failed to become amplified and generate progeny particles. The virus could be rescued when NS proteins were supplied in trans, showing that P4 hyperactivity in S is needed to reach a level of NS-1 expression that is sufficient to drive the viral replication cycle. These data show that E2F-mediated P4 activation at the early S phase is a limiting factor for parvovirus production. The primary barrier to parvovirus gene expression in G1 is thought to be promoter formation rather than activation, due to the poor conversion of the parental single-strand genome to a duplex form. The S dependence of P4 activation may therefore be a sign of the virus adaptation to life in the S-phase host cell. If the conversion block in G1 were to be leaky, the S induction of promoter P4 could be envisioned as a safeguard against the production of toxic NS proteins until cells reach the S phase and provide the full machinery for parvovirus replication.
Gesehen am 11.02.2021